Angel with two faces : a mystery featuring Josephine Tey - Upson, Nicola (Upson, Nicola. Josephine Tey mystery., 2010)
Real-life British mystery writer Josephine Tey returns as a fictional sleuth in Angel with Two Faces<U+2014>the second atmospheric mystery in Nicola Upson<U+2019>s wonderfully inventive series. In this riveting sequel to Expert in Murder, Tey, in league with intrepid policeman Detective Inspector Archie Penrose, is called upon to help unravel a dark and perplexing crime at a Cornwall country house and backstage at a local theater. Fans of P.D. James and of British noir in general will adore Angel with Two Faces<U+2014>a traditional mystery with a twist<U+2014>and this writer whom Ms. James herself calls, “A new and assured talent.”